Thyroid nodule malignancy is associated with increased non-invasive hepatic fibrosis scores in metabolic subjects - Crudele, Lucilla; Novielli, Fabio; De Matteis, Carlo; Petruzzelli, Stefano; Suppressa, Patrizia; Berardi, Elsa; Antonica, Gianfranco; Piazzolla, Giuseppina; Sabbà, Carlo; Graziano, Giusi; Moschetta, Antonio (Frontiers in Oncology, 2023)
Introduction: Thyroid cancer incidence is increasing and adiposity-related conditions are gaining space in its pathogenesis. In this study, we aimed to detect any anthropometric, bio humoral and clinical features that might be associated with thyroid nodules malignancy, potentially representing novel non-invasive markers of thyroid cancer. Materials and Methods: The study was conducted in a group of 142 consecutive out-patients (47 males, 95 females) who underwent Fine Needle Aspiration Biopsy/Cytology (FNAB/C) in the suspicion of malignancy from January 2018 to September 2022. We compared lipid and glycaemic blood profile as well as non-invasive liver fibrosis indexes such as AST to ALT ratio (AAR), AST to Platelet Ratio Index (APRI), Fibrosis Index Based on 4 factors (FIB-4), between patients with benign and malignant newly diagnosed nodules. Then, we performed ROC analysis to assess their best cut-offs for discrimination of malignant nodules and chi-squared test to evaluate the association of specific dysmetabolic conditions to malignancy. To understand whether and to what degree dysmetabolic conditions increased the risk of thyroid nodules malignancy, we also calculated the Odds Ratio (OR) of main biomarkers. Results: After FNAB/C, 121 (85%) patients were diagnosed with benign thyroid nodules, while 21 (15%) individuals were diagnosed with thyroid cancer. Comparing patients with benign and malignant nodules, we found that individuals with thyroid cancer exhibited increased BMI (p=0.048), and fasting glycemia (p=0.046). Intriguingly, considering non-invasive scores for liver fibrosis, subjects with thyroid cancer presented increased AAR (p<0.001) and APRI (p=0.007) and these scores were associated to malignancy (p<0.005) with a OR=7.1 and OR=5, respectively. Moreover, we showed that only in cancer group, low levels of Vitamin D correlated with stigmata of impaired metabolism. Discussion: In our study, AAR and APRI scores are associated with thyroid nodules malignancy and could be used to predict it and to speed up the diagnostic process. From a pathogenic point of view, we speculated that metabolic-associated fatty liver disease (MAFLD) along with hyperglycaemia and Vitamin D deficiency may represent putative drivers of thyroid carcinogenesis.